Do They Get What They Want or Are They Stuck With What They Can Get? Testing Homophily Against Default Selection for Friendships of Highly Aggressive Boys. The TRAILS Study - Lindenberg, Siegwart M. (Journal of abnormal child psychology, 2010)
In this study a homophily selection hypothesis was tested against a default selection hypothesis, to answer whether preferred and realized friendships of highly aggressive boys differed. In a large peer-nomination sample, we assessed who highly overt aggressive, low prosocial boys (n = 181) nominated as friends (preferred friendships) and who among the nominated friends reciprocated the friendship (realized friendships). These preferred and realized friendships were compared with those of less aggressive (n = 1,268) and highly aggressive but also prosocial boys (bi-strategics; n = 55). Results showed that less aggressive boys preferred peers low on aggression, whereas highly aggressive and bi-strategic boys preferred peers not particular high or low on aggression. In line with default selection, highly aggressive boys ended up with aggressive peers even though that was not their preference. In general, received support proved an important determinant of highly aggressive, bi-strategic, and less aggressive boys’ preferred and realized friendships. Especially highly aggressive boys preferred emotionally supportive friends, but ended up with the least supportive peers. In sum, for friendships of highly overt aggressive boys, the evidence favors default selection over homophily selection